Features of distance teaching for technical disciplines - Аfanasieva О.; Lalazarova, N.; Goncharova, S. (New Collegium, 2021)
The features of the use of new technologies for distance learning, which potentially increase the possibilities of the educational process, in particular, in the study of technical disciplines, are considered. This problem is relevant at the present time, when the entire system of higher and secondary education is temporarily working in a distance or mixed mode. For distance education, most universities use the Moodle virtual learning environment. Teaching students is carried out using computer technologies and various ways of presenting information: text, graphics, video, soundtrack, animation, that is, what is called "multimedia". In the process of mastering the distance course, the student can perform various types of activities  acquaintance with theoretical material, laboratory and practical work, assignments, compiling a dictionary, communication in forums and chat rooms. Working with a distance course requires in-depth study of the material in the process of independent work. Distance education increases the number of activities for students of various forms of education that cannot be foreseen in the traditional study of the discipline due to the limited classroom hours, which makes it possible to improve the quality of education. Distance education increases the number of activities for students of various forms of education that cannot be foreseen in the traditional study of the discipline due to the limited classroom hours, which makes it possible to improve the quality of education. The distance course can be used for full-time students as the main method of teaching, as it is currently due to quarantine, or as an auxiliary, for example, only for those students who do not attend classes, for in-depth study of the material, for students with disabilities. physical capabilities. The lack of Ukrainian standards for the distance learning system does not allow the creation of materials in a unified learning environment. But each educational institution can, on its own initiative, create distance courses in a particular environment, transfer certain types of classes to distance learning, look for new opportunities and forms of implementation of information and training technologies.